Discretion and Its Limits—An Analytical Framework for Understanding and Applying the Duty of Care to Corporate Directors (and Others) - Philip C. Sorensen (Washington University Law Quarterly, 1988)
This Article begins with an examination of the peculiar state of corporate directors and their duty of care. It next examines discretionary authority and its limits, including the question of whether discretionary authority might be merely an illusion, or perhaps a by-product of other interests sought to be served. I conclude that it is neither. This Article next analyzes the claim of corporate directors to discretionary authority. It proposes and tests against typical cases standards of conduct that measure two crucial factors, limits of discretion and economic utility. Finally, it explores the adaptability of the proposed tests to the current legal framework.
Keywords: Executives